Designing a Marketing Strategy for Samarium 153 ethylenediaminetetramethylene phosphonic acid (Sm 153-EDTMP) for Palliative Treatment of Cancer that Spreads to The Bones - Wida Rahayu; Wahono Sumaryono; Sri Widyastuti; Henky Lesmana (PT Mattawang Mediatama Solution, 2023)
This research is proposed to identify marketing strategic of Samarium ethylenediaminetetramethylene phosphonic acid (Sm 153-EDTMP) that is used for palliative treatment of bone metastasis towards utilization policy by the Nuclear Medicine Doctors. The data is obtained from the questionnaire that were spread out to Nuclear Medicine Doctors in a number of Hospital in Indonesia as respondents. The respondents were 35 of Nuclear Medicine Doctors. This number represents 80 % of Nuclear Medicine Doctors population in Indonesia. The research methodology is accomplished by descriptive explorative analysis. The results are: (1) dose, side effect of Sm 153-EDTMP that is more tolerating than morphine, (2) according to the local product promotion, Sm 153-EDTMP is able to be delivered more effectively to the user through detailing, symposium, internet (3) the price of the local product of Sm 153-EDTMP that is way more cheaper than morphine. By paying attention to marketing strategies through product advantages, promotional forms and prices SM 153-EDTMP shows that these products can be used by Nuclear Medicine specialists (SpKN) as a palliative treatment for cancer that spreads to the bones.